In situ-grown hexagonal silicon nanocrystals in silicon carbide-based films - Kim, Tae-Youb (Springer, 2012)
Silicon nanocrystals (Si-NCs) were grown in situ in carbide-based film using a plasma-enhanced chemical vapor deposition method. High-resolution transmission electron microscopy indicates that these nanocrystallites were embedded in an amorphous silicon carbide-based matrix. Electron diffraction pattern analyses revealed that the crystallites have a hexagonal-wurtzite silicon phase structure. The peak position of the photoluminescence can be controlled within a wavelength of 500 to 650 nm by adjusting the flow rate of the silane gas. We suggest that this phenomenon is attributed to the quantum confinement effect of hexagonal Si-NCs in silicon carbide-based film with a change in the sizes and emission states of the NCs.